CLINICAL SIGNIFICANCE OF INTRAOPERATIVE NEUROPHYSIOLOGICAL MONITORING DURING SCOLIOSIS SURGERY: A LITERATURE REVIEW - Sylvia Tanumihardja; Dedeh Supantini; Julia Windi Gunadi; Ardo Sanjaya; Katherine Marcella (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Mechanical damage to nerve fibers during scoliosis correction can result in severe neurological disorders. It has been demonstrated that intraoperative neurophysiological monitoring during spinal surgery reduces the risk of motor deficits or paraplegia. Despite significant advances in the technique and application of IONM (intraoperative neurophysiological monitoring), data reporting the impact of implementing intraoperative neurophysiological monitoring on scoliosis surgery intervention remains very limited. Therefore, this review aims to investigate the correlation between the application of IONM and the risk of neurologic deficits in scoliosis patients undergoing surgery. The database sourced from PubMed (Jan 2010 to Jan 2022) was used to identify all studies evaluating the effectiveness and impact of intraoperative neurophysiological monitoring during scoliosis surgery and reducing the risk of postoperative complications. This systematic review included five studies. Multimodal IONM, with its high sensitivity and specificity, provides an objective benchmark that surgeons can implement to review surgical strategies to reduce the risk of permanent neurologic deficits. Multimodal IONM can be considered the gold standard of IONM in scoliosis surgery to prevent neurological damage and provide a more satisfactory result of surgical intervention.